Comparative analysis for fractional nonlinear Sturm-Liouville equations with singular and non-singular kernels - Ercan, Ahu (Amer Inst Mathematical Sciences-Aims, 2022)
This article presents the Laplace-Adomian decomposition method (LADM), which produces a fast convergence series solution, for two types of nonlinear fractional Sturm-Liouville (SL) problems. The fractional derivatives are defined in the Caputo, conformable, Caputo-Fabrizio in the sense of Caputo (CFC), Caputo type Atangana-Baleanu (ABC) senses. With the help of this method, approximate solutions of the investigated problems were obtained. The solutions generated from the Caputo and ABC derivatives are represented by the Mittag-Leffler function, which is intrinsic to fractional derivatives, and the solution obtained using the conformable and CFC derivatives generate the hyperbolic sine and cosine functions. Thus, we derive some novel solutions for fractional-order versions of nonlinear SL equations. The fractional calculus provides more data than classical calculus and has been widely used in mathematical modeling with memory effect. Finally, we analyzed and compared these novel solutions of the considered problems by graphs under different values of p, lambda and different orders of alpha.
Keywords: nonlinear Sturm-Liouville equation; Laplace-Adomian decomposition method; Caputo; conformable; Caputo-Fabrizio; Atangana-Baleanu fractional derivatives